The Challenge of Foreign Fighter Returnees - Cragin, R. Kim (Journal of contemporary criminal justice, 2017)
This article explores the security challenges posed by foreign fighter returnees. It argues that—contrary to popular belief—most foreign fighters do not die on battlefields or travel from conflict to conflict. They return home. This means that law enforcement, intelligence, and other security officials should expect unprecedented numbers of returnees from Syria and Iraq should a ceasefire hold. The challenge posed by returnees is threefold: Recidivism rates are uncertain, law enforcement cannot manage the numbers of prospective returnees alone, and returnees from non-Western countries also pose a threat to the United States. Findings suggest that a global architecture should be put in place to mitigate the threats from foreign fighter returnees.